Generations of Faith: A Congregational Atlas - Eeman, Carl G. (Rowman & Littlefield Publishers, 2002)
In 1991 a pair of Ivy League-educated Californians, William Strauss and Neil Howe, published a landmark book, Generations: The History of America's Future from 1584 to 2069. In Generations and subsequent books, they develop a theory that generational cycles repeat through American history at about 90- to 95-year intervals. In this book, Carl Eeman accepts the invitation of Strauss and Howe in Generations: "We encourage specialists among our readers, whatever their backgrounds, to shed more light on the component pieces of the generational puzzle" (p. 16). Eeman explores the cycle of four generational types from a faith perspective and applies generational ideas to the practice of ministry and to congregational issues. This book makes use of the young field of generational theory and provides a valuable tool for understanding between generations. As congregational leaders minister among the people of God, these concepts will help them be more effective leaders, clearer communicators, and more nimble troubleshooters and problem solvers. Foreword by William Strauss and Neil Howe.